As metamorfoses recentes no espaço urbano de Senador Canedo: rearranjos nos espaços da metrópole goiana - LIMA, Leandro Oliveira de (2010)
The study of urban space is basic to understand the actual society, as the world population is increasing more and more in the cities. The construction of these cities, made by different actors, give strong fragmenting features, articulated by the capitalist mode of production. The Brazilian Central-Western region, of fundamental importance in the national economy, site of two planned cities by modern urbanism (Goiânia and Brasília), is also an attractive pole for people and services that provide a range of urban problems for the two cities and its hinterlands. Moreover, the insertion of Goiás in the national productive process, made by the conservative and concentrated modernization, significantly rearranged the production of the space of Goiás, providing the industrialization of some cities over others, especially those assorted with infrastructure such as the cities of southeastern Goiás. The town of Senador Canedo (originated from the construction of the railroad and landing herds) appears in this context and is not alien to economic processes experienced intrastate. Thus we aimed to analyze the historical process of socio-spatial territorialized in the town of Senador Canedo, understanding that the proximity to the city interfered with the logic and with the historical growth of the canedense urban area, causing serious administrative problems. Besides we seek to highlight the important role of Senador Canedo in the metropolitan area of Goiânia (RMG) as a satellite town, considering the process of becoming city of the capital of Goiás. Senador Canedo contributes with approximately 75 million people (IBGE estimates to 07/2008) in the metropolitan context, as the municipality with the highest population growth rate (9.3%) of the RMG (3.2%) between 1991 and 2000. The methodology of the research will review the literature related to urban themes and specific study of the city to provide subsidies on the construction of the city and its daily reproduction. The field research, from interviews and questionnaires and the mapping aimed the reconstruction of the socioespacial history and the mapping of the city and the implications of the hegemonic logic of capital in the urban canedense. The regionalization of the data analysis will allow the analyse and reconstitution of the appropriation of the city from the intraurban scale. By this methodology we understand the structuring of socio-spatial Senador Canedo taking into account the form of reproduction that the capitalist model of directed consume has led their action on the city beyond realizing that the hegemonic process of metropolization is interfering in the internal dynamics of Senador Canedo.